9
15
27
33
Correct answer is A
a = u2 - 3y2 = (1)2 - 3(-1) = -2 b = 2uu + v2 + v2 = 2(1)(-1) + (-1)2 = -1 ∴ 2(2a - b)(a - b∴) = [2(-2) - 1](-2 - (-1)2) = -3 - 3 = 9
If the distance between the points (x, 3) and (-x, 2) is 5. Find x ...
Simplify 35÷(27×43÷49) ...
In a recent zonal championship games involving 10 teams, teams X and Y were given probabilities \(\f...
In the diagram, PQRS is a parallelogram. Find the value of < SQR ...
Simplify: x2−5x−14x2−9x+14 ...
A kite flies on a taut string of length 50m inclined at tan angle 54o to the horizontal ground. The ...
While doing his physics practical, Idowu recorded a reading as 1.12cm instead of 1.21cm. Calculate h...
The area A of a circle is increasing at a constant rate of 1.5 cm2s−1. Find, to 3 significan...
Simplify (p−r)2−r22p2−4pr...
Factorise (4a + 3) 2 - (3a - 2)2...
Numerical Reasoning Questions and Answers
Data Interpretation Questions and Answers
Nigeria General Knowledge Questions and Answers
Typing Speed and Accuracy Test
Abstract Reasoning Questions and Answers
Personality Test
Spatial Reasoning Questions and Answers
Microsoft Office Questions and Answers
Quantitative Reasoning Questions and Answers
Verbal Reasoning Questions and Answers
Situational Judgement Questions and Answers
Puzzles Questions and Answers
Logical Reasoning Questions and Answers
See all →